News framing of the U.S. immigration debate during election years: Focus on generic frames. Issue 2 (3rd April 2018) - Kim, Jeesun; Wanta, Wayne
ABSTRACT: This study examined the frames used in the news coverage of the U.S. immigration debate during election years. Stories from four major U.S. newspapers, the Los Angeles Times, the St. Louis Post-Dispatch, the St. Petersburg Times, and The New York Times, were content analyzed. The analysis revealed that the conflict frame was the most dominant frame in the news coverage of the U.S. immigration debate whereas no significant changes in the framing of the U.S. immigration debate were found over time. The human interest frame was more likely to have a pro-immigration tone compared to other frames. The findings of immigrant characteristics showed that the "illegal" characteristic was the most frequently used to identify immigrants.